Jørgen Døør (Ecolinguística: Revista brasileira de ecologia e linguagem (ECO-REBEL), 2022)
Jørgen Døør was born in 1933 in Copenhagen, Denmark. Studies of Philosophy and Psychology, University of Copenhagen; Mathematics and Nordic Languages, Teachers Training College, Copenhagen. Head of Department, University of Southern Denmark. (OU 1966-1997). At present: Free-lance researcher, novelist (published 14 novels with his wife,  Dorte Bay Madsen), pacifist, vegetarian, and ecological activist.